Painless Project Management with FogBugz - Gunderloy, Michael (Apress : Imprint: Apress, 2007)
Project management is the bane of the team approach to programming. Many programs out there purport to help a development team manage a project; the only trouble is, most of them aren't very good. World-renowned software guru Joel Spolsky's company, Fog Creek Software, has created a tool called FogBugz that incorporates all of Joel's insight into what works and what doesn't work in project management. FogBugz is based on keeping track of a database of cases. At any given time, every case is assigned to one person who must resolve it or forward it to someone else. Cases can be prioritized, documented, sorted, discussed, edited, assigned, estimated, searched, and tracked. Because FogBugz is web-based, everyone on the team always sees the whole picture. Everything from customer feature requests to high-level design discussions to tiny bug fix details is instantly searchable and trackable. Painless Project Management with FogBugz, Second Edition, written with the guidance of the whole FogBugz team, completely describes the ins and outs of version 6 of FogBugz.